2016
DOI: 10.1155/2016/9729275
|View full text |Cite
|
Sign up to set email alerts
|

Bioguided Fraction and Isolation of the Antitumor Components fromPhyllanthus niruriL.

Abstract: Phyllanthus niruri L., a well-known medicinal plant, has been used as a folk antitumor remedy in the worldwide scale. However, the antitumor components in P. niruri have not been reported. In order to verify the antitumor components of P. niruri and the plants which have the high content of these components, we isolated the antitumor components with bioguided fraction and isolation, by different chromatographic methods from the ethyl acetate fraction of P. niruri., and identified them as ethyl brevifolincarbox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 25 publications
(29 reference statements)
2
31
0
2
Order By: Relevance
“…Furthermore, the δ C values at 164.2, 166.3 and 167.7 revealed the presence of carbonyl carbons at C 7 , C 7' and C 7" respectively. All the spectroscopic data were in accordance with the reported literature 7 and on that basis, this compound was confirmed as corilagin.…”
Section: Resultssupporting
confidence: 88%
“…Furthermore, the δ C values at 164.2, 166.3 and 167.7 revealed the presence of carbonyl carbons at C 7 , C 7' and C 7" respectively. All the spectroscopic data were in accordance with the reported literature 7 and on that basis, this compound was confirmed as corilagin.…”
Section: Resultssupporting
confidence: 88%
“…The present study further identified that corilagin is a major active component from P. niruri L. extracts and has broadspectrum antitumor activity, a better antitumor potential but lower toxicity to normal cells (12). It is effective in retarding the growth of hepatocarcinoma cells by inducing G2/M phase arrest (9); inhibiting ovarian cancer cells via TGF-β/AKT/ERK signaling pathways (10); and suppressing cholangiocarcinoma progression through the Notch signaling pathway (11).…”
Section: Introductionmentioning
confidence: 86%
“…Corilagin was extracted and purified by the Xiamen Overseas Chinese Subtropical Plant Introduction Garden as previously described (12).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, cancer is always a big challenge to cure, and avoiding its recurrence following treatment, whether by using chemotherapy, phototherapy, or combinatorial therapies, needs more research for the exploration of potential anticancer drugs from natural sources. The plants in the genus Phyllanthus are well-known to possess medicinally active ingredients and have long been used as traditional antitumor remedies throughout the world [ 63 ]. Various chronic diseases such as cancer, hepatitis and diabetes mellitus have been well treated with P. amarus extracts in traditional medication systems in China [ 52 ].…”
Section: Biological Activitiesmentioning
confidence: 99%
“…Moreover, the antitumor components of P. niruri have been reported for the first time and the presence of ethyl brevifolincarboxylate and corilagin identified. P. niruri -derived corilagin has wide antitumor potential on HCC cells and the results proved it is a superior antitumor agent causing the least harm to normal and neighbouring cells [ 63 ].…”
Section: Biological Activitiesmentioning
confidence: 99%